Narcolepsy and pregnancy: a retrospective European evaluation of 249 pregnancies. (8th April 2013) - Maurovich‐Horvat, Eszter; Kemlink, David; Högl, Birgit; Frauscher, Birgit; Ehrmann, Laura; Geisler, Peter; Ettenhuber, Katharina; Mayer, Geert; Peraita‐Adrados, Rosa; Calvo, Elena; Lammers, Gert Jan; Van der Heide, Astrid; et al.
Summary: In a retrospective cohort study undertaken in 12 European countries, 249 female narcoleptic patients with cataplexy ( n = 216) and without cataplexy ( n = 33) completed a self‐administrated questionnaire regarding pregnancy and childbirth. The cohort was divided further into patients whose symptoms of narcolepsy started before or during pregnancy (308 pregnancies) and those in whom the first symptoms of narcolepsy appeared after delivery (106 pregnancies). Patients with narcolepsy during pregnancy were older during their first pregnancy ( P < 0.001) and had a higher body mass index (BMI) prior to pregnancy ( P < 0.01). Weight gain during pregnancy was higher in narcoleptic patients with cataplexy ( P < 0.01). More patients with narcolepsy–cataplexy during pregnancy had impaired glucose metabolism and anaemia. Three patients experienced cataplexy during delivery. The rate of caesarean sections was higher in the narcolepsy–cataplexy group compared to the narcolepsy group ( P < 0.05). The mean birth weight and gestational age of neonates were within the normal range and did not differ across groups. Neonatal care was affected adversely by symptoms of narcolepsy in 60.1% of those with narcolepsy during pregnancy. This study reports more obstetric complications in patients with narcolepsy–cataplexy during pregnancy; however, these were not severe. This group also had a higher BMI and higher incidence of impaired glucose metabolism during pregnancy. Caesarian section was conducted more frequently in narcolepsy–cataplexy patients, despite cataplexy being a rare event during delivery. Furthermore, symptoms of narcolepsy may render care of the infant more difficult.